Closed Digital Artery Injury in Children: A Case Report and Review of the Literature. Issue 4 (April 2020) - Bougie, Emilie; Cugno, Sabrina
Abstract : Abstract: Closed digital artery injury is a very rare phenomenon, even more so in children, with only 5 cases reported in the literature. We report a case of closed digital arterial interruption in a child after crush injury to the left hand. We further discuss possible etiologies and describe adequate management as found in the pertinent literature. Digital arterial injury should be suspected even in closed hand trauma because a delay in recognition may lead to devastating consequences.